Heat [videorecording (Blu-Ray)] - Mann, Michael, 1943-; Pacino, Al, 1940-; De Niro, Robert; Sizemore, Tom, 1961-2023; Venora, Diane; Brenneman, Amy; Judd, Ashley; Williamson, Mykelti; Studi, Wes; Levine, Ted; Voight, Jon, 1938-; Kilmer, Val, 1959-; et al. (20th Century Fox Home Entertainment LLC, 2017)
Vincent Hanna is a brilliant L.A. cop, following the trail from a deadly armed robbery to a crew headed by master thief Neil McCauley. The trouble is, McCauley's expertise is at least equal to Hanna's.